Social anthropology: investigating human social life - Barnard, Alan (New Delhi : Viva Books Private Limited, 2007)
Social Science
Keywords: Social anthropology; Human life; Ethnography; Ecology; Economics; Politics and law; Sex and Gender; Development anthropology